Intraspecific facilitation explains the spread of the invasive engineer Spartina anglica in Atlantic salt marshes. (15th March 2019) - Proença, Barbara; Nez, Tanya; Poli, Armand; Ciutat, Aurélie; Devaux, Ludovic; Sottolichio, Aldo; de Montaudouin, Xavier; Michalet, Richard
Abstract: Questions: Invasiveness depends in part on the ability of exotic species to either exclude native dominants or to fill an empty niche. Comparisons of niches and effects of closely related native and invasive species enable the investigation of this topic. Does Spartina anglica invade European salt marshes through competitive exclusion of the native Spartina maritima or due to the occurrence of an empty ecological niche in highly anoxic conditions? Study Site: The Arcachon Bay (France). Methods: At three intertidal levels, we quantified competitive response and effect abilities of the two species through a cross‐transplantation removal experiment. We also compared the biomass, root/shoot ratio, productivity and environmental conditions (elevation, salinity, redox potential and soil moisture) of salt marsh communities dominated by the exotic Spartina anglica or the native Spartina maritima at three intertidal levels. Results: Both established species showed similar biotic resistance to the invasion of the other species, but the exotic showed important intraspecific facilitation for growth. Species had similar niches and total biomass along a gradient of anoxic conditions, but the exotic had a much higher root/shoot ratio and productivity than the native. Owing to its rhizome density, the exotic showed high ability to increase sediment oxygenation, likely to explain its important intraspecific facilitation. Conclusions: Our results showed that the invasion success of S. anglica cannot be explained by the competitive exclusion of the native or by its ability to fill an empty niche along a gradient of anoxia. Its behaviour as a self‐facilitator invasive engineer very likely explains its rapid spread in the Bay and biotic resistance to the colonization of other congeneric species when established in dense patches. Additionally, we suggest that physical disturbance in marsh communities dominated by the native S. maritima may disrupt its biotic resistance against the invasion of S. anglica . Abstract : With a cross‐transplantation removal experiment, we have assessed the competitive effects and responses of two Spartina species in a European salt marsh. We showed that the native Spartina maritima had a strong biotic resistance to the invasion of Spartina anglica . However, once installed, the exotic Spartina anglica exhibited a self‐facilitating behaviour and strong competitive ability that favoured its spread.